SHARING THE READING SECRET: USING THINK-ALOUD TO IMPROVE READING COMPREHENSION OF L2 TEXTS - Hamed Barjesteh (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2010)
This study investigates the effects of thinking-aloud on L2 reading inrelation with the type of task Iranian EFL readers engage in whilereading activity. In so doing, 360 students were selected and assignedto experimental and comparison groups. The subjects in experimentalgroups were instructed to verbalize whatever they were thinking astheir thought naturally came to mind while reading and doing theassigned tasks. The results indicated that the instructional procedurehad contributed to the improvement of the EFL students’ readingcomprehension. By and large, the analysis of think-aloud protocol canprovide language learners with a means for monitoring their readingprocess. Moreover, it gives an opportunity for language teachers tobecome more sensitized to various comprehension problems thatstudents encounter and offers clues to understand potential weaknessthat students may have in their L2 reading.